Conceptual framework for precision cancer medicine in Germany: Consensus statement of the Deutsche Krebshilfe working group 'Molecular Diagnostics and Therapy'. (August 2020) - Westphalen, C. Benedikt; Bokemeyer, Carsten; Büttner, Reinhard; Fröhling, Stefan; Gaidzik, Verena I.; Glimm, Hanno; Hacker, Ulrich T.; Heinemann, Volker; Illert, Anna L.; Keilholz, Ulrich; Kindler, Thomas; Kirschner, Martin; et al.
Abstract: Precision cancer medicine (PCM) holds great promises to offer more effective therapies to patients based on molecular profiling of their individual tumours. Although the PCM approach seems intuitive, multiple conceptional and structural challenges interfere with the broad implementation of PCM into clinical practice. Accordingly, concerted national and international efforts are needed to guide the further development and broad adoption of PCM in Germany. With support of the 'German Cancer Aid' ( Deutsche Krebshilfe [DKH] ) a task force ' Molecular Diagnostics and Therapy' was implemented. In two workshops supported by the DKH, delegates from the fourteen comprehensive cancer centresidentified key topics essential to implement quality-guided, harmonized and adaptable PCM. Based on an online questionnaire and using a modified Delphi approach, nine statements were drafted and evaluated within the group. These statements could serve as a basis to define a collaborative strategy for PCM in the future with the aim to sustain and further improve its quality. Highlights: This consenus statement originated from collaborative efforts of all fourteen Comprehensive Cancer Centres in the German Cancer Aid network. The consensus statement is based on all centres' consent due to implementation of a modified Delphi process. This consensus statement will serve as a framework to establish sustainable structures for precision cancer medicine in Germany.